Hubungan Cultural Competency Tenaga Kesehatan dalam Layanan Homecare dengan Cultural Safety pada Masyarakat yang Berbeda Suku - Yusnaini, Yusnaini; Karo, Dina Andriani Br.; Ayuni, Dini Qurrata; Elvira, Mariza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the relationship between the cultural competency of health workers in homecare services and cultural safety in communities of different ethnicities in Babussalam District, Southeast Aceh Regency. The method used is correlation analytical research with a cross-sectional approach. The research results show that there is a relationship between the cultural competency of health workers in homecare services and cultural safety in communities of different ethnicities with a p-value of 0.016. In conclusion, health workers who have good cultural competency can implement good cultural safety. Therefore, it is recommended that health facility managers support health workers by providing cultural competency training and cross-cultural communication skills as well as forming a representative team of health workers from various ethnic groups in the region. Keywords: Cultural Competency, Cultural safety, Homecare.